Diabetes mellitus and hypertension: a dual threat. (July 2016) - Oktay, Ahmet Afşin; Akturk, Halis Kaan; Jahangir, Eiman
Abstract : Purpose of review: The following is a review of the current concepts on the relationship between hypertension (HTN) and diabetes mellitus with a focus on the epidemiology and cardiovascular prognostic implications of coexistent HTN and diabetes mellitus, shared mechanisms underlying both conditions and pathophysiology of increased risk of cardiovascular disease, treatment of HTN in individuals with diabetes mellitus, and effects of anti-diabetic medications on blood pressure (BP). Recent findings: Diabetes mellitus and HTN often coexist in the same individual. They share numerous risk factors and underlying pathophysiologic mechanisms, most important of which are insulin resistance and inappropriate activation of the rennin–angiotensin–aldosterone system. Recently updated guidelines recommend a BP goal of 140/90 mmHg in most individuals with diabetes mellitus. A new class of anti-diabetic medications, sodium–glucose co-transporter 2 inhibitors, has shown favorable effects on BP. Summary: HTN affects the majority of individuals with diabetes mellitus. Coexistence of diabetes mellitus and HTN, especially if BP is not well controlled, dramatically increases the risk of morbidity and mortality from cardiovascular disease. BP control is an essential part of management of patients with diabetes mellitus, because it is one of the most effective ways to prevent vascular complications and death.